International Cooperation on Search and Rescue in the Arctic - Sydnes, Are Kristoffer; Sydnes, Maria; Antonsen, Yngve (Arctic Review on Law and Politics, 2017)
International Cooperation on Search and Rescue in the Arctic SAR in the Arctic is a complex and dynamic cross-disciplinary activity that requires the combined effort of multiple actors with specialized human and technical resources. Due to limited resources and infrastructure in the Arctic, international cooperation is particularly important. This article applies a conceptual framework drawn from regime-theory to study SAR cooperation in the Arctic. More specifically, we apply the three dimensions of regime effectiveness (outputs, outcomes and impacts) to examine the regimes established by the 2011 Arctic SAR Agreement and the 1995 Barents SAR Agreement. The study addresses the rights and duties established by the regimes and their institutional arrangements for cooperation. Further, it investigates the importance of operational cooperation among response agencies in understanding the development and effectiveness of the regimes. The study concludes that the Arctic SAR regime is still under implementation. The agreement has entered into force but a series of steps needs to be taken for the common SAR system to be operative. Consequently, the regime is in the early stages of development and any evaluations of its impact are premature. The parties have implemented the Barents SAR regime both formally and in practice. Though the regime is generally held to have a positive effect on cooperation between the parties, there is a range of challenges that raise questions regarding its capacity to provide for a coordinated and effective joint SAR operation. The study further concludes that treating regime effectiveness in terms of a causal link between output, outcome and impact should be done with caution. It also argues that the focus of regime theory on interest-based decision-making among regime parties should be supplemented by investigating the operative and informal aspects of cooperation.